The new content of primary education in Kazakhstan: testing and experience. (Journal of Educational Sciences, 2017)
This article discusses the practice of implementation of the new State compulsory standard of primary education (hereinafter – SCSPE) in some pilot schools involved in piloting the updated programme. In accordance with the order dated from April 3, 2015 № 159 «On the pilot implementation of the updated curriculum» a new SCSPE was piloted in Grade 1 of 30 pilot schools in the 2015-2016 academic year. Virtually, such update occurs on average every 10-15 years in all developed countries. The main differenceof the new SCSPE is that it is focused on building a model based on learning outcomes in contrast to the previous «knowledge centered» models. The article addresses the issue of curriculum content and textbooks that have been revised within the new SCSPE. The article outlines the main challenges encountered by the teachers of pilot schools in the process of piloting the updated curriculum based on the qualitative empirical research results. The findings support the idea of taking a complex set of measures focused on revisingthe content of some subjects and improving the quality of textbooks.
Keywords: new primary school curriculum; new SCSPE; secondary education; Grade 1